Highly stable and efficient mRNA templates for mRNA–protein fusions and C-terminally labeled proteins - Miyamoto-Sato, Etsuko (Oxford University Press, 2003)
For high-throughput in vitro protein selection using genotype (mRNA)–phenotype (protein) fusion formation and C-terminal protein labeling as a post-selection analysis, it is important to improve the stability and efficiency of mRNA templates for both technologies. Here we describe an efficient single-strand ligation (90% of the input mRNAs) using a fluorescein-conjugated polyethylene glycol puromycin (Fluor-PEG Puro) spacer. This ligation provides a stable c-jun mRNA with a flexible Fluor-PEG Puro spacer for efficient fusion formation (70% of the input mRNA with the PEG spacer) in a cell-free wheat germ translation system. When using a 5′ untranslated region including SP6 promoter and Ω29 enhancer (a part of tobacco mosaic virus Ω), an A(8) sequence (eight consecutive adenylate residues) at the 3′ end is suitable for fusion formation, while an XA(8) sequence (XhoI and the A(8) sequence) is suitable for C-terminal protein labeling. Further, we report that Fluor-PEG N-t-butyloxycarbonylpuromycin [Puro(Boc)] spacer enhances the stability and efficiency of c-jun mRNA template for C-terminal protein labeling. These mRNA templates should be useful for puromycin-based technologies (fusion formation and C-terminal protein labeling) to facilitate high-throughput in vitro protein selection for not only evolutionary protein engineering, but also proteome exploration.